The Phylogenetic Analysis of Biofilm Producing, Multi Drug Resistant P.Aeruginosa Isolated from Different Clinical Cases - Saadiyah Abed Jaddoa, Mithal Ka. Al-Hassani, (Pakistan Journal of Medical & Health Sciences, 2022)
To perform this study, out of 32 Pseudomonas aeruginosa isolates, about 20 multi-drug resistant isolates were selected, diagnosed firstly depending on their cultural, microscopic, and biochemical characteristics, then the diagnoses had been confirmed through 16s rRNA gene. The Kirby-Bauer method of antibiotic sensitivity test were performed, by using an eleven common antibiotics, and the results were as the following, the resistance ratios of Ampicillin and Amoxicillin were 100%, which is mean that all isolates were resistant to these two antibiotics, the resistance ratio reached 90% for the Pipracillin, the resistance ratio of Cefepime and Ceftazidime was 70%, the resistance ratio of Ciprofloxacin was 65%, the resistance ratios of Amikacin and Tobramycin were 45%, 40%, respectively, the resistance ratio of Aztreonam was 35%, the resistance ratio of meropenem was 20%, finally, the resistance ratio of Imipenem was 10%, that represent the lowest resistance ratio, so in this study Imipenem was the most efficient antibiotic. The phylogenetic tree analysis showed the following results, for the gene 16S rRNA, there is a great similarity between our two local isolates and other global isolates, the phylogenetic tree analysis of the gene algD showed a low similarity when compared with the global isolates, while the phylogenetic tree analysis of the gene pelF showed both high and low similarities, whereas the degree of similarity between our two local isolates and the global isolates for the gene pslD ranged between 79% and 99%.